Analysis of the coach's behavior in relation to effective and noneffective players in basketball - Rosado, A.; Mesquita, I. (International Journal of Performance Analysis in Sport, 2009)
The present study's objective was to analyze the Portuguese Basketball coaches' behavior in relation to players' status (effective and noneffective). Twenty two male basketball teams participated. The teams belonged to the National Basketball League of the 1st and 2nd division (16 teams). The sample consisted of junior and senior players (N=199). We used an observational category system called "Observation System of the Coach's Behavior" (O. S. C. B.). 92 sessions were filmed in audio and video register. The recordings had duration between 90 and 120 minutes. The procedure used for data collection in this study was time duration recording and event recording. The reliability of the observations was assured by the inter-observer and intra-observers agreement, within a 15-day interval. The results showed that coaches' behaviors are differentiated in accordance to the athlete's status. There were four categories where significant differences existed, the average value being superior in the effective players. The coaches observed more, corrected more and interacted more with the effective players. Effective players received, also, more positive evaluations. We concluded that the coaches have not the same behavior with all members of the team, differentiating in accordance to their game capacities.